Prognostic value of immune-related genes and comparative analysis of immune cell infiltration in lung adenocarcinoma: sex differences - Tao Fan (BMC, 2021)
Highlights 1. We presented a detailed and comprehensive analysis of immune cell infiltration in tumor microenvironment (TME) of female and male patients with lung adenocarcinoma (LUAD). 2. We compared the differences in the tumor immune microenvironment between female and male LUAD patients. 3. The density of memory B cells in TME of female patients with LUAD was significantly higher than that of male patients, which may explain that female patients with LUAD have a better prognosis than that of male patients. 4. We identified immune-related genes that predicted the prognosis of female and male LUAD patients, respectively, and their predictive value were verified by another independent cohort.